Design, optimization, characterization, and in vivo evaluation of sterosomes as a carrier of metformin for treatment of lung cancer. (2nd April 2020) - Osama, Hasnaa; Sayed, Ossama M.; Hussein, Raghda R. S.; Abdelrahim, Mohamed; A. Elberry, Ahmed
Abstract: The present study aimed to formulate and evaluate metformin sterosomes. Sterosomes were prepared by incorporating stearylamine and cholesterol in different ratios. Sterosomes were characterized using size, zeta potential, entrapment efficiency (EE%) and in vitro release. Aerosol generated by nebulization was evaluated by a cooled Andersen cascade impactor (ACI) at 15 L/min. In vitro cytotoxicity of free and metformin-containing sterosomes was tested against human cancer cell lines. A comparative pharmacokinetic study between sterosomal formulation and free drug solution (750 mg) was performed. Spirometry was performed before and at time intervals after inhalation. The mean hydrodynamic diameter of the formulated vesicles was in the range of 288.7–578 nm. The EE% varied from 71 ± 1.4% to 89 ± 5.2%, with an optimum EE% of 89 ± 5.2at a lipid ratio of 2/1 stearylamine/cholesterol. Metformin sterosomes displayed an inhibitory effect on A549 lung cancer cell lines which significantly ( p < 0.05) increased depending on dose and prolonged exposure time. Spirometric data were minimally changed before and after inhalation without a statistically significant difference in the forced expiratory volume in one second (FEV1 ), forced vital capacity (FVC) or FEV1 /FVC ratio ( p > 0.05). Metformin-loaded sterosomes resulted in a significant increase in biological half-life ( t 1/2 ) with a mean value of 7.31 ± 1.04 h compared to 3.99 ± 0.17 h of the solution form. However, the peak plasma concentration of metformin sterosomes was lower than that achieved by metformin-free solution aerosol, and the difference was statistically significant ( p < 0.05).The eligibility of sterosomes for aerosol delivery by nebulization would provide a novel strategy for delivery of metformin by inhalation as a potentially effective inhalation treatment of lung cancer.